(untitled) (Biological Sciences - PJSIR, 2004)
Tylenchorhynchus fatimae sp.n was collected around the roots of coconut field, Malir and coconut plants from PCSIR campus, Karachi is described and illustrated. T. fatimae sp.n comes close to T. brassicae (Siddiqi 1961), T. tuberosus (Zarina and Maqbool 1994), T. tritici (Golden et al 1969) and T. rubustoides (Thorne and Malek 1968) but differs in stylet length, general shape of the body and DGO. Geocenamus rugosus (Thorne and Malek 1968) Brezeski 1991 is reported for the first time from Pakistan are listed. Measurements of Geocenamus rugosus are given from paratype and rest of the measurements from illustration are mentioned in Table 1.